Liolaemus rothi : cannibalism - Kozykariski, Monica Lilian (2009)
Liolaemus rothi is a stout, medium-sized liolaemid lizard found in northern Patagonia (Neuquén, Río Negro, and Chubut provinces) in steppe or steppe-Monte ecotone habitats on rocky substrates. Though some authors mention it to be insectivorous, dietary data are scarce (Cei 1986. Reptiles del Centro, Centro-Oeste y Sur de la Argentina, Monogr. IV, Mus. Reg. Sci. Nat. Torino, Italy. 527 pp.). Here, we report an observation of intraspecifi c saurophagy in L. rothi.